Sensitivity analysis of space-based water vapor differential absorption lidar at 823 nm - Barton-Grimley, Rory A.; Nehrir, Amin R. (Frontiers in Remote Sensing, 2024)
Measurements of water vapor are important for understanding the hydrological cycle, the thermodynamic structure of the lower troposphere, and broader atmospheric circulation. Subsequently, many scientific communities have emphasized a need for high accuracy and spatial resolution profiles of water vapor within and above the planetary boundary layer (PBL). Advancements in lidar technologies at the NASA Langley Research Center are ongoing to enable the first space-based water vapor differential absorption lidar (DIAL) that can provide high accuracy and vertical resolution retrievals of moisture in the PBL and through the mid-troposphere. The performance of this spacebased DIAL is assessed here for sensitivity throughout the troposphere and globally with representative canonical cases of water vapor and aerosol loading. The specific humidity retrieval sensitivity to systematic and random error is assessed and measurement resolutions and capabilities are provided. We show that tunable operation along the side of the 823 nm absorption line allows for optimization of the lower tropospheric water vapor retrievals across different meteorological regimes and latitudes and provides the operational flexibility needed to dynamically optimize random errors for different scientific applications. The analysis presented here suggests that baseline and threshold systematic error requirement of <1.5 % and <2.5 %, respectively, are achievable. Random error is shown to dominate the retrieval with errors on the order of 5% within the PBL are achievable with 300 m vertical 50 km horizontal resolutions over open ocean and on the order of 10-15% over high albedo surfaces. The flexibility of the DIAL method to trade retrieval precision for spatial resolution is shown, highlighting strengths over passive techniques to tailor retrievals to different scientific applications. Combined, the total error budget demonstrated here indicates high impact for space-based DIAL with technologies being advanced for space-missions within the next 5-10 years.